2024
DOI: 10.1021/acs.macromol.3c01888
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain-Functionalized Poly(indacenodithiophene-alt-benzothiadizole)s as Stretchable High-Mobility Semiconductors with Improved Elasticity

Bin Zhao,
Dandan Pei,
Yibo Shi
et al.

Abstract: To regulate the mechanical properties of poly-(indacenodithiophene-alt-benzothiadizole) (IDT-BT), a highmobility polymer semiconductor with high ductility but inferior elasticity (plastic deformation onset strain (PdOS) < 10%), triisopropylsilyl (TIPS), hydroxyl (OH), and 2-ureido-4[1H]pyrimidone (UPy) groups were introduced into its side chain ends. The incorporation of bulky and neutral TIPS groups led to slightly increased ductility but had no obvious influence on the elasticity of the polymer. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that H-bonding units featuring nucleobase-derived structures, such as thymine (Thy), ureidopyrimidinone, and diaminopyrimidine (Dap), are particularly effective due to their ability to engage in multipoint H-bonding. ,,, These units form dimeric interactions, significantly enhancing the H-bonding effects in the conjugated polymers. Additionally, positioning these units at the end of side chains in a pendant-type structure has proven to be a successful approach to retain the overall conjugation of the polymer backbone, thus preserving the essential electronic properties of the polymers. ,, For instance, we have demonstrated the benefits of strategically incorporating Thy units at the end of the side chains of PM7-based conjugated copolymer donors, which facilitated H-bonding-assisted intermolecular interactions without disturbing the electronic performance . The resulting intrinsically stretchable organic solar cells (IS-OSCs) achieved a high power conversion efficiency (PCE) of 13.7% and exhibited excellent stretchability, maintaining 80% of their initial PCE even at 43% strain.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that H-bonding units featuring nucleobase-derived structures, such as thymine (Thy), ureidopyrimidinone, and diaminopyrimidine (Dap), are particularly effective due to their ability to engage in multipoint H-bonding. ,,, These units form dimeric interactions, significantly enhancing the H-bonding effects in the conjugated polymers. Additionally, positioning these units at the end of side chains in a pendant-type structure has proven to be a successful approach to retain the overall conjugation of the polymer backbone, thus preserving the essential electronic properties of the polymers. ,, For instance, we have demonstrated the benefits of strategically incorporating Thy units at the end of the side chains of PM7-based conjugated copolymer donors, which facilitated H-bonding-assisted intermolecular interactions without disturbing the electronic performance . The resulting intrinsically stretchable organic solar cells (IS-OSCs) achieved a high power conversion efficiency (PCE) of 13.7% and exhibited excellent stretchability, maintaining 80% of their initial PCE even at 43% strain.…”
Section: Introductionmentioning
confidence: 99%